Non-Refoulement Through Local Wisdom: Indonesia’s International Legal Compliance as a Non-Ratifying State in Handling Rohingya Refugees in Aceh - Roesa, Nellyana; Rosmawati, Rosmawati; Listriani , Sophia; Zaidi Daud , Mohd; Mahfud, Mahfud (Uti Possidetis: Journal of International Law, 2026)
Abstract Background: The legal issue of handling Rohingya refugees in Indonesia arises from the gap between the official state policy of rejecting the presence of Rohingya refugees, citing their non-ratification of the convention, and Aceh's social empathy for Rohingya refugees. Aceh's social acceptance and concern for Rohingya refugees stem from Acehnese local wisdom known as "Peumulia jamee" and the seafaring custom of "Panglima Laot." Aceh's social values ​​are equated with the principle of non-refoulement in international refugee law. This principle is part of the theory of substitute protection, the concept of well-founded fear, and the theory of shared burden in handling international refugees. Methodology The method used in this research is normative legal research, using a legislative approach, principles, concepts, and related theories. This study aims to analyze how Indonesia handles Rohingya international refugees as a Non-Participating State of the Legal Regime of the 1951 Convention on the Status of Refugees and the 1967 Protocol and how the synergy between Indonesia's national policies and Aceh's local wisdom and Indonesia's official legal policies as a Non-Participating State. Objectives: This segment outlines the key goals of the research. The author should specify the intended outcomes and the research questions that guided the study.  Findings: The research results show that a number of approaches have been taken by Indonesia to handle Rohingya refugees, in the form of unifying the international mandate regarding the handling of Rohingya refugees in Indonesia. Originality/Novelty: A more local approach oriented toward redefining the concept of Laot Customary Law (Pemulia Jamee), particularly the concept of "Pemulia Jamee," is due to the vastly different dimensions and jurisdictional scope of customary and state law, which are cross-border in nature. Indonesia must also continue to advocate for the plight of Rohingya refugees at international levels, such as the UN and ASEAN, through humanitarian diplomacy, resolving the root causes of the conflict in Myanmar, and urging the international community to share the burden.